"Isolation of Clostridum botiulinum (Types A, B, E) in Sediments from Coastal Areas in the North of Iran" - HR Tavakoli; V Razavilar (Tehran University of Medical Sciences, 2003)
Iranian J Publ Health, Vol. 32, No. 3, pp.37-40, 2003 Isolation of Clostridum botiulinum (Types A, B, E) in Sediments from Coastal Areas in the North of Iran *HR Tavakoli 1,V Razavilar 2 1Dept. of Nutrition and Food Hygiene,School of public health, Baghyatollah University of Medical Sciences, Tehran, Iran 2Dept. of Food Hygiene, School of Veterinary Medicine, Tehran University , Iran Clostridium botulinum has long been recognized as an etiological agent of food borne botulism and has been reported as an important food safety hazard. The aim of this study was to obtain information about C. botulinum distribution in north areas sediments of Iran in order to ascertain the risks associated with consumption and processing of fish from these waters. Two hundred and seventy samples of sediments from coastal areas of "Gilan" and "Mazandaran" provinas of Iran were collected and analyzed. The supernatants were inoculated into cooked meat media and then , grown specimens were stained and cheked microscopically. After centrifuge ,the supernatants were divided into three (untreated ,heated , and tripsinised )and toxicity of them were tested by mouse bioassay. All mice controlled for 4 days for symptoms of botulism. Monovalent standard antitoxins were used for detection of toxin type. The present study revealed that the prevalence of C. botulinum (types A, B and E) in sediments from different areas of Gillan and Mazandaran was 3.6% and 4.6% respectively, Mean prevalence of C. botulinum in sediments from north regions of Iran was 4.1%. It is also demonstrated that C. botulinum type E is predominant type seen in aquatic environments of the coastal areas of Iran. This is the first report of C. botulinum distribution in the sediments coastal areas of Iran. Introduction *Corresponding author: +98 21 4811483